Fluorouracil-containing formulations

JP2025026953AActive Publication Date: 2025-02-26SISAF LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024201958
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-03-28
Filing Date
2024-11-20
Publication Date
2025-02-26
Estimated Expiration
2040-03-30

Smart Images

  • Figure 2025026953000001
    Figure 2025026953000001
  • Figure 2025026953000002
    Figure 2025026953000002
  • Figure 2025026953000003
    Figure 2025026953000003
Patent Text Reader

Abstract

To provide a topical formulation containing fluorouracil and not exhibiting contact sensitization.SOLUTION: A pharmaceutical composition for use in treatment of superficial basal cell carcinoma, actinic keratosis, solar keratosis, acne or scars comprises pharmaceutically compatible nanoparticles and at least 0.5 wt.% of fluorouracil, where the nanoparticles comprise at least 50 wt.% of hydrolyzable silicon and are surface-coated with phospholipid, the coated nanoparticles are associated with fluorouracil, the fluorouracil is electrostatically associated with the surface of the nanoparticles and / or the phospholipid bilayer, and the nanoparticles are associated with a willow bark extract.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to improved topical formulations containing fluorouracil and uses thereof. It is. [Background technology]

[0002] Fluorouracil (international generic name) is the chemical 5-fluoro-2,4(1H,3H)- Fluorouracil is a pyrimidinedione that is useful as an anticancer agent, and is used in the treatment of breast, bladder and Fluorouracil has also been used in the systemic treatment of various cancers, including those of the pancreas and the liver. To treat basal cell carcinoma, actinic keratosis, solar keratosis and various forms of scarring and severe acne Topical preparations containing fluorouracil are currently available. Although effective, it can cause side effects, the main ones being skin irritation and Associated pain, ulcers, and erythema. There is a need for improved formulations that provide effective transdermal dose delivery.

[0003] U.S. Patent No. 6,670,335 describes fluorouracil as a "microsponge In porous microparticles, called "particles of ethylenediaminetetraacetate," and in emulsions, presumably due to their hydrophilicity. The present invention discloses the use of a formulation consisting of an oil-in-water emulsion, which is also present in the aqueous phase of the emulsion. is.

[0004] There is a need for improved delivery systems for local administration of fluorouracil. It continues to exist.

[0005] The present invention provides silicon particles with improved properties over those of U.S. Pat. No. 6,670,335. The nanoparticles were used to effectively combine silicon nanoparticles and fluorouracil with excellent properties. The nanoparticles are then assembled into a single nanoparticle. The waxy fatty acid ester is encapsulated in a lipid matrix containing the waxy fatty acid ester. The drug is virtually free of fluorouracil and has excellent bioavailability upon administration. It can be processed into a powder suitable for a variety of topical formulations to reduce side effects.

[0006] Silicon Nanoparticles Several methods have been developed to deliver active pharmaceutical ingredients in a controlled or sustained manner. However, once the function of delivering and releasing the active ingredient is fulfilled, the carrier material ultimately The present invention provides a method for the administration of silicone-based carrier materials that can be used to treat a variety of conditions, including the development of beneficial effects after administration. A delivery system that converts the

[0007] To enable local delivery of active ingredients, considerable research has been conducted to develop a method for controlling the delivery of active ingredients to the stratum corneum. The focus has been on developing methods to temporarily disrupt the cellular barrier, resulting in drugs that It is possible to deliver a sufficient amount of blood to the blood vessels, reaching a therapeutic level. Some technologies, such as ultrasound, have been explored as dermal absorption enhancers. However, most attempts have focused on the use of reversible endothelial cell membranes to allow large amounts of drugs to penetrate the skin. Our research has focused on identifying non-toxic chemical penetration enhancers that can interact with the barrier. Early attempts to destroy it used single solvents or solvent mixtures, surfactants and fatty acids. These substances can enhance the skin permeation of many chemicals, but not all of them are desirable. These are often associated with unpleasant side effects, which may be caused by extracting or removing components of the skin. It elicited a stimulus response by combining it with the ability to interact with the

[0008] Silicon is an essential trace element for plants and animals. It is essential for mammals. Composition of protein-glycosaminoglycan complexes found in the matrix of connective tissues Structural role as a nutrient and metabolic role in growth and bone formation (presence of silicon Silicon is therefore essential for bone and connective tissue. Silicon is also essential for the normal development of tissue. It is known to act as a collagen and elastin promoter and an antioxidant in the body. Silicon is involved in the synthesis of glycosaminoglycans and silicon-dependent The benefits of the natural tissue building process are increased by the intrinsic enzymes.

[0009] For medical applications, silicon can be produced as microparticles or nanoparticles, Microparticles or nanoparticles can be delivered via a number of routes, including topical ingestion, oral ingestion, injection, or implantation. Biodegradable silicon-based particles can also be used for drug targeting. However, the bioavailability of silicon is often limited by its poor solubility. and organic silicon-containing materials tend to exhibit unacceptably high toxicity. Its uses are limited to cosmetic, skin care and pharmaceutical applications.

[0010] Porous silicon was discovered by Arthur Ulrich at Bell Laboratories in the United States. It was first discovered by chance in 1956 by Hir Jr. and Ingeborg. The production of high-quality silicon begins with its initial formation, followed by the immersion of a single crystal in a hydrofluoric acid (HF) solution. or polycrystalline silicon, dye etching or anodizing cells. By forming pores in silicon, the material is decomposed and the silicon is activated into pores. The use of porous silicon as a carrier for other active compounds is possible. The use of cyclosporine has been described (Saffie-Siebert R et al., Drug Disco very World 2005; 6: 71-6; Saffie-Siebert , R et al., Pharmaceutical Technology Europe, 17(4), 21-28 (2005); Luo, D., Saltzman, WM, Gene Therapy (2006) 13, 585-586; Ahola, M., Kortesuo, P., Kangasniemi, I. , Kiesvaara, J., Yli-Urpo, A., Int. J.P. harm. 195 (2000) 219 227. Ahola. M., Sai lynoja, ES, Raitavuo, MH, Vaahtio, M .H., Salonen, J.I., Yli-Urpo, AUO, Bi. omat. (2001), 15, 2163-2170; Lu, J., Li ong, M., Zink, J., Tamanoi, F. Small. 20 07, 3: 1341-1346). However, the decomposition products of such carrier systems It is also important to note that silicon-containing support systems are particularly important in that they can be used without polymerization. , which breaks down to form the effective and bioactive form of silicon, orthosilicic acid. preferable.

[0011] The dissolution product of silicon in an aqueous environment is silicic acid, which has the general formula [SiO x ( OH) 4-2x ] n A general family of chemical compounds of the elements silicon, hydrogen, and oxygen It is a typical name. Metasilicic acid (H 2 SiO 3 ), orthosilicic acid (H 4 SiO 4 , at 25°C pK a1 = 9.84, pK a2 =13.2), metadisilicate (H 2 S 2 O 5 ) and pyro Silicic acid (H 6 S 2 O 7 Some single silicic acids, such as silicic acid, have been identified in sufficiently dilute aqueous solutions. , and silica (SiO 2 The silicic acid polymer (PolySA) with It stands for silicic acid in monomeric form, alternatively monosilicic acid. Orthosilicic acid (OSA), also known as d), and silica, where silica is energetically favorable. The silicon-based reaction is shown on the opposite side, showing the optimal morphology. The concentration and pH determine the direction of the reaction and the monomer formation. , and the equilibrium state between the polymer and the silica.

[0012] [ka]

[0013] Silicic acid can be considered a buffer molecule. Orthosilicic acid (OSA) is a very weak acid. , weaker than carboxylic acids, for example. Orthosilicic acid (OSA) has a pK at 25 °C: 1 dissociates at 9.84.

[0014] [ka]

[0015] Silicic acid has a pKa of about 9.8, so it is a mixture of ionized and undissociated acids in solution. The ionized species (H 3 SiO 4 - ) acts as a proton scavenger, removing it from solution. It removes protons, thus raising the pH of the solution. On the other hand, the undissociated species is hydroxide i.e. This raises the pH of the solution because it can donate a proton to neutralize the ion. Thus, silicic acid buffers the solution. This buffering capacity develops rapidly at low Si concentrations. It is worth noting that high Si concentrations lead to low pH, which leads to dimerization. Body (H 6 S 2 O 7 ), or by allowing silicic acid to undergo condensation reactions to form higher order structures and water. These dimers and higher-order structures (SiO x OH y ) is the hydroxide ion in the solution By reacting with the amine, the pH is lowered and the amine can return to its monomeric or lower structure. Similarly, these polymerized acids can be further enhanced by neutralizing hydroxides at high pH. Therefore, polysilicic acid can act as a buffer, but the reaction is proportional It is very slow.

[0016] Silica [SiO 2 ] indicates the end of complete polymerization of OSA, decreasing its solubility and Thus, it reduces bioavailability, biodegradability and safety.

[0017] Enthalpy of dimerization and further polymerization reactions at biological pH and ambient temperature Therefore, polymerization generally proceeds via:

[0018] [ka]

[0019] This is a reversible process, so the reverse reaction from silica to OSA is theoretically possible. However, it requires a pH value above 13 and high temperatures, which means that it is thermodynamically ineffective under physiological conditions. It is not scientifically suitable.

[0020] The reaction of OSA with itself to form silica occurs when two OSA molecules are combined in solution. In this case, OH - The concentration is increased to the point where it becomes similar to a dimer of silicic acid that associates with ions and dissociates. The limiting concentration of the pure solution containing only silicic acid is about 10 -4 Mol.L -1 (Studies of the kinetics of f the precipitation of uniform silica pa rticles through the hydrolysis and conde nsation of silicon alkoxides, Journal of Colloid and Interface Science, Volume 1 42, Issue 1, March 1, 1991, pages 1-18 GH Bogush and CF Zukoski IV), above this concentration, other PolySA species However, at high concentrations, the formation of ol Tosilicic acid can be prevented from polymerizing through the addition of other chemical species.

[0021] [ka]

[0022] The kinetics of dissolution, ignoring surface area, depends on the pH and availability of reactive species. The main reactive species in the gas phase is water in both protonated and deprotonated forms ( Kinetic data on reaction rates in both directions are given by Brinker "Sol-gel sc However, other molecules Addition of will shift the equilibrium to silicic acid or silicon oxide (glass) depending on the pKa value of the other molecule. It can shift significantly and produce side reactions.

[0023] Although dissolution can be controlled by adjusting the pH for storage purposes, the pH in the body varies depending on the body. Therefore, the adjustment of dissolution rate by particle size and surface chemistry is This must be done before use in the body. Protonation or Hydroxylated silicon is preferred. It is desirable to slow down the dissolution of silicon particles. In the preferred embodiment, an oxide layer of appropriate thickness provides a lag in dissolution characteristics as the oxide layer slowly dissolves. The thickness of this oxide layer determines the length of the delay period before water can access the silicon core. Determine.

[0024] Since the binding of drug molecules is highly dependent on surface energy, care must be taken when treating silicon surfaces. may be necessary.

[0025] The growth of oxide on the surface increases the contact angle, favoring the binding of hydrophobic molecules and polarizing On the other hand, surface hydroxylation reduces the molecular binding between the silicone surface and the drug molecule. The contact angle between the surface and the surface is reduced, favoring the binding of hydrophilic molecules such as fluorouracil.

[0026] OSA is a very weak acid that is unstable at pH levels below 9.5 and is harmful to the human body. It quickly precipitates or forms a sol or gel that is largely bioavailable. It is very difficult to prepare highly concentrated solutions (greater than 0.5% silicon) of silicic acid and oligomers. Furthermore, the type of silicic acid produced by the formulation is different from that of silicic acid, silicon compounds, etc. This dissolution is determined in large part by the concentration of acetaminophen and the pH of the medium in which it occurs. To achieve this, the concentration of silicic acid must be strictly controlled.

[0027] WO 2011 / 012867 describes stabilized silicon-based materials as advantageous compounds. The stabilization is carried out with polysilicic acid (poly By reducing the production level of SA, elemental silicon is converted into biologically active orthosilicic acid. By carrying out procedures to control the decomposition of the product, the safety of the product is improved.

[0028] The present invention relates to a schizophrenia stabilized with a stabilizer by the method of WO 2011 / 012867. The advantages that the ribon nanoparticles contribute to the invention of WO 2011 / 012867, namely This not only provides improved degradation of bioavailable OSAs, but also improves their stability. The fluorouracil stabilized silicon nanoparticles were loaded with sufficient The present invention also provides a method for binding and delivering fluorouracil so that it can be stored and released on demand, and a method for stabilizing fluorouracil. The silicon nanoparticles were then encapsulated in a waxy lipid to produce a powder containing solid particles. A process involving the decomposition of silicones such as waxy lipids and This is particularly possible by a process in which the fluorouracil and any surrounding medium are substantially free of fluorouracil. This is based on the fact that the amount of fluorouracil that is not associated with the particles is This is in contrast to the formulation of U.S. Patent No. 6,670,335, which is significantly more abundant. This results in dose dumping of fluorouracil into the skin after the first dose. This reduces the side effects of burning and irritation on the skin surface while still providing a therapeutic effect. It is then possible to administer a dose that satisfies the above requirement.

[0029] The advantage of using silicon nanoparticles, which are smaller than the microparticles of the prior art, is that the silicon material itself The body determines the size of the biocompatible, biodegradable, and optionally highly porous nanoparticles by determining whether the particles are small or Blocking the pilosebaceous ostra or sweat ducts (pores) The small size of the nanoparticles can be made to be 20-400 nm, which is ideal for skin delivery. This allows the particles to actively target the base of the hair follicle rather than simply acting as a reservoir of drug on the surface. It is a highly adjustable formulation that can be penetrated.

[0030] The use of silicon nanoparticles eliminates the need for waxy polymers that would otherwise only be suitable for hydrophobic compounds. Hydrophilic fluorouracil is loaded onto hydrophobic waxy powder particles, also known as microspheres. Because it is formulated, it is particularly suitable for use in compositions containing fluorouracil. do. [Prior art documents] [Patent documents]

[0031] [Patent Document 1] U.S. Patent No. 6,670,335 [Patent Document 2] International Publication No. 2011 / 012867 [Non-patent literature]

[0032] [Non-Patent Document 1] Saffie-Siebert R et al., Drug Discovery World 2005; 6: 71-6 [Non-Patent Document 2] Saffie-Siebert, R et al., Pharmaceutical Technology Europe, 17(4), 21-28 (2005) [Non-Patent Document 3] Luo, D., Saltzman, W.M., Gene Therapy (2006) 13, 585-586 [Non-Patent Document 4] Ahola, M., Kortesuo, P., Kangasniemi, I., Kiesvaara, J., Yli-Urpo, A., Int. J. Pharm. 195 (2000) 219 227 [Non-Patent Document 5] Ahola. M., Sailynoja, ES, Raitavuo, MH, Vaahtio, MH, Salonen, JI, Yli-Urpo, AUO, Biomat. (2001), 15, 2163-2170 [Non-Patent Document 6] Lu, J., Liong, M., Zink, J., Tamanoi, F, Small. 2007, 3: 1341-1346 Summary of the Invention [Means for solving the problem]

[0033] According to a first aspect, the present invention provides a method for producing a phospholipid-coated glycerin-based food product comprising: 1. A pharma- ceutically compatible nanoparticle comprising a hydrolyzable silicone surface of The nanoparticles provide nanoparticles associated with fluorouracil.

[0034] According to a second aspect, the present invention provides a pharma- ceutically compatible nanoparticle according to the first aspect of the invention. A pharma- ceutically compatible powder comprising solid particles of one or more waxy fatty acid esters encapsulated therein. 90% or more by weight of the composition is fluorouracil, optionally coated nanoparticles. Preferably, the powder comprises salicylic acid, e.g., powder may include willow bark extract.

[0035] According to a third aspect, the present invention provides a pharmaceutical composition suitable for topical administration to the skin or other body surfaces. A pharma- ceutically compatible cream or gel according to the second aspect of the invention. The cream or gel comprises a cream or gel base in which a powder is suspended.

[0036] According to a fourth aspect, the present invention is an adhesive patch comprising a backing layer and an adhesive film. The adhesive film is then coated with a pharma- ceutical compatible powder according to the second aspect of the invention or The present invention provides an adhesive patch comprising the cream or gel according to the third aspect of the present invention.

[0037] According to a fifth aspect, the present invention provides a compound according to the first aspect of the invention for use as a medicament. and a pharma- ceutically compatible powder according to the second aspect of the invention. A pharma- ceutically compatible cream or gel according to the third aspect of the invention and a pharmaceutical composition according to the fourth aspect of the invention. Provide adhesive patches.

[0038] According to a sixth aspect, the present invention relates to a method for treating superficial basal cell carcinoma or actinic keratosis, solar keratosis, scarring. or a pharmaceutical composition according to the first aspect of the invention for use as a medicament for treating acne. A medicament for preparing a medicament according to the second aspect of the invention and a medicament according to the third aspect of the invention. a pharma- ceutically compatible cream or gel according to the first aspect and an adhesive according to the fourth aspect of the invention. Provide a patch.

[0039] According to a seventh aspect, the present invention relates to a method for treating superficial basal cell carcinoma or actinic keratosis, solar keratosis, scarring. or a pharma- ceutical composition according to the first aspect of the present invention for the manufacture of a medicament for treating acne. and a pharma- ceutically compatible powder according to the second aspect of the invention and a pharma- ceutically compatible powder according to the third aspect of the invention. and a pharma- ceutically compatible cream or gel according to the fourth aspect of the invention. Provides tips and tricks.

[0040] According to an eighth aspect, the present invention provides a method for treating superficial basal cell carcinoma or actinic keratosis, solar keratosis, scarring. Or a method for treating acne, comprising administering to a subject a pharma- ceutical compatible composition according to the third aspect of the present invention. or applying a therapeutically effective amount of a cream or gel according to the fourth aspect of the invention. The present invention provides a method of treatment comprising administering a patch to a subject. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] definition According to the present disclosure, a derivative of a compound is one that has substantially the same structure but contains one or more substitutions. For example, one or more chemical groups may be added, deleted, or modified to have a different group. In certain preferred embodiments, the derivatives retain the pharmaceutical activity or activity of the compound from which they are derived. has at least a portion of the cosmetic activity, e.g., at least 90% of the activity of the compound from which it is derived; Holding 80%, 70%, 60%, 50%, 40%, 30%, 20% or 10%. In some embodiments, the derivatives have increased pharmaceutical or cosmetic activity compared to the compound from which they are derived. It can be shown that the

[0042] For example, in the context of a peptide, a peptide derivative refers to a peptide having one or more additional amino acid residues, It may include peptides that have been deleted or substituted with alternative amino acid residues. The substitutions may be conservative or non-conservative, although conservative substitutions are preferred.

[0043] According to a first aspect, the present invention provides a silicone composition comprising at least 50% by weight of hydrolyzable silicone. lipids (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidyl Ethanolamine, components of lecithin and one or more of their derivatives, especially phosphatidyl Coating the surface with one or more of choline, hydrogenated phosphatidylcholine and its derivatives The pharma- ceutically compatible nanoparticles are coated with fluorous Nanoparticles associated with Rasil are provided.

[0044] The phospholipid coating preferably modifies the hydrolysis rate of the silicon and / or The phospholipid coating inhibits the rate of polymerization of silicic acid. It is preferred to suppress the rate of decomposition.

[0045] In one embodiment, the hydrolysis rate of the silicon-containing material is increased by the hydrolysis of a phospholipid (e.g., a phospholipid). Phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidylethanolamine, One or more of the components of choline and their derivatives, in particular phosphatidylcholine, hydrogenated phosphatidylcholine, The presence of acetylcholine and one or more of its derivatives increases the rate of phospholipid synthesis. The hydrolysis rate of the same composition is less than 50%, preferably less than 30%, and more preferably less than 10%. will be changed to

[0046] The rate of hydrolysis can be determined by the rate at which the OSA is assimilated in the body or removed from the delivery site, e.g., by diffusion. By slowing the reaction rate to a level lower than that required for polymerization of the OSA, polymerization of the OSA can be avoided or at least It has been found that the blood flow to the brain can be reduced and the beneficial effects of delivering OSA to the body can be achieved.

[0047] The decomposition products of monomeric silicic acid are naturally available in the human body, so the present invention The use of the product results in a very low risk of toxins, which is different from many other delivery systems. The delivery system of the present invention provides a significant advantage over known beneficial biological processes. Another advantage is that the carrier is degraded to provide a bioavailable composition. For example, OSA induces cytotoxicity in certain cell types, including fibroblasts, endothelial cells, and keratinocytes. It is known to stimulate cell proliferation and cell migration.

[0048] Advantageously, the nanoparticles according to the invention (e.g. phosphatidylcholine, hydrogenated phosphatidylcholine) One of the components of lecithin, phosphatidylcholine, phosphatidylethanolamine, and their derivatives At least one of these, particularly phosphatidylcholine, hydrogenated phosphatidylcholine and derivatives thereof Bioavailable orthosilicic acid obtained by decomposition of nanoparticles coated with one or more However, it is also used by itself as a nutrient for skin, bones, hair, nails, connective tissue, and for treating arthritis or bone It is effective in treating or preventing bone or joint diseases such as porous tissue.

[0049] Silicon nanoparticles with a phospholipid coating on the surface, especially the phospholipid coating, When in the form of a bilayer of one or more phospholipids, it is particularly suitable for associating with fluorouracil. It has been found that this association is preferably caused by the attraction between opposite charges. For example, the charges of the phospholipid bilayer and / or the surface of the silicon nanoparticles and the fluorescein can be determined by the charge of the phospholipid bilayer and / or the surface of the silicon nanoparticles. The electrostatic association between the charges of lauricil In a preferred embodiment relating to all aspects of the present invention, According to the invention, the association is promoted by the presence of amino acids, and therefore all products of the invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidylethanolamine) One or more of the following compounds may be used: amines, components of lecithin and their derivatives, in particular phosphatidylcholine The surface of the nanoparticles is coated with one or more of phosphatidylcholine, hydrogenated phosphatidylcholine and its derivatives. The cellulose particles are preferably made of amino acids, in particular arginine or a mixture of arginine and glycine. Includes things.

[0050] The presence of amino acids (e.g., one or more of arginine and glycine) also enhances the affinity of silicon nanoparticles to the silicon nanoparticles. Stabilize the charge on the surface of the particles and use phospholipids (e.g., phosphatidylcholine, phosphatidyl phosphate). Phosphatidylcholine, phosphatidylethanolamine, lecithin components and their derivatives one or more of the following, in particular phosphatidylcholine, hydrogenated phosphatidylcholine and derivatives thereof One or more of the fluorouracils are useful for improving the association with the fluorouracil. The presence of amino acids improved the release of fluorouracil and the stability and dispersibility of silicone over time. In its broadest sense, the term "amino acid" refers to Any artificial or naturally occurring amine (-NH 2 ) functional group and carboxyl (-COOH The term "amino acid" includes organic compounds containing α, β, γ and δ functional groups. The term "amino acid" includes amino acids of any chiral configuration. In some embodiments, naturally occurring alpha amino acids are preferred. Proteinogenic or non-proteinogenic amino acids (carnitine, levothyroxine, Arginine may also be used. It is particularly preferred that the glycine or arginine mixture contains glycine. It is preferred that 30% of the amino acids are arginine.

[0051] Therefore, preferred pharma- ceutically compatible nanoparticles of the present invention (e.g., phosphatidylcholine Ingredients include phosphatidylcholine, hydrogenated phosphatidylethanolamine, lecithin, and and one or more of their derivatives, in particular phosphatidylcholine, hydrogenated phosphatidylcholine and its derivatives) are coated with The nanoparticles are then coated with fluorouracil and (preferably arginine, glycine and mixtures thereof). and most preferably selected from both arginine and glycine. It is something like that.

[0052] The nanoparticles of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, and Nanoparticles coated with one or more of these derivatives, the nanoparticles being full Nanoparticles associated with oleuracil, and optionally with one or more of arginine and glycine. The presence of willow bark extract associated with the nanoparticles also improved the association of fluorouracil with the nanoparticles. (Willow and / or White Willow, preferably Willow bark extract (derived from Willow salicylic acid) is a compound that traps fluorouracil. This leads to increased association of fluorouracil with the nanoparticles. This provides that when the nanoparticles are delivered to a treatment site, e.g. When the molecule is delivered locally to the skin surface, such as in a cream or gel, It should help ensure that emissions are controlled. Bark extracts usually contain salicin, which is metabolized to form salicylic acid, an antioxidant. It is known to exhibit anti-inflammatory and antioxidant activities.

[0053] According to a preferred embodiment, fluorouracil is present in the products of all aspects of the invention. At least 80% by weight, for example at least 90% by weight, of the coated nanoparticles ( For example, phosphatidylcholine, hydrogenated phosphatidylcholine, and one of their derivatives. The coated nanoparticles are provided with fluorouracil associated therewith. , willow bark extract, and / or one or more of arginine and glycine. The nanoparticles can also be associated with amino acids.

[0054] Molecular association between fluorouracil and phospholipid-coated silicon nanoparticles Advantageously, when the silicon nanoparticles or their coating are decomposed, the fluorine is released. This ensures that louracil is bioavailable. The rate of hydrolytic degradation is determined by the major components. The rate of release can be controlled, so the rate at which fluorouracil becomes bioavailable can be controlled. In addition, it is also possible to prevent dose-dumping and / or prevent nanoparticles from escaping from the skin surface. The aim is to ensure limited release when the drug advances to a site distant from the target (e.g., the basal site). can be controlled by

[0055] Nanoparticles according to all aspects of the invention (e.g., phosphatidylcholine, hydrogenated phosphatides, etc.) Nanoparticles coated with one or more of acetylcholine and its derivatives, The nanoparticles are associated with fluorouracil, willow bark extract, and / or arginine and The nanoparticles (which can also be associated with one or more amino acids, such as one or more of glycine and glycine) are porous and For example, the porosity may be determined by dividing the surface area by the surface area of ​​a non-porous material of comparable size. The surface area may be increased by at least 1.5, 2, 2.5, 3, 3.5 or 4 times.

[0056] Phospholipids Phospholipids for use in accordance with all aspects of the present invention (e.g., phosphatidylcholine, Hydrogenated phosphatidylcholine, phosphatidylethanolamine, lecithin and other ingredients and one or more of the derivatives thereof, in particular phosphatidylcholine, hydrogenated phosphatidylcholine and its derivatives. The silicone derivatives are dissolved in water, for example in phosphate buffered saline (PBS). Optionally alter, e.g. reduce or eliminate, the rate of hydrolysis of the organic substance; and / or Once formed, such a polymer is formed by suppressing the polymerization rate of the OSA to produce an inert carrier. Thus, phospholipids are compounds that stabilize OSA in aqueous solutions, e.g. , especially in commonly used aqueous buffers such as Tris or phosphate buffered saline. Hydrolysis of the containing material promotes the formation of OSA and / or the silicon-containing material remains After hydrolysis, it can be an agent for suppressing the polymerization rate of OSA in aqueous solution.

[0057] Generally, PBS contains the following components: NaCl 137 mM, KCl 2.7 mM, Contains 10 mM basic sodium phosphate, 2 mM potassium dihydrogen phosphate, and pH 7.4. PBS is used as a model of physiological conditions at a temperature of 37°C.

[0058] As mentioned above, silicones are hydrolyzed in aqueous media to OSAs, which are then subsequently synthesized into OSAs of various chain lengths. and polymerize into molecular entities of the structure, ultimately forming water-insoluble silicates. The product is designed to optimize the biodegradation process so that polymerization of the formed OSA is substantially inhibited. In this way, the decomposition products are stabilized and their properties, especially solubility and viscosity, are The bioavailability is controlled to maximize bioavailability by chemical modification of the nanoparticle surface. That is, the surface is treated with a phospholipid stabilizer (e.g., phosphatidylcholine, phosphatidyl phosphate, etc.). and optionally one or more acetylcholine and their derivatives. Coating by surface association with amino acids (e.g., one or more of arginine and glycine) Optionally, the nanoparticles are also associated with a willow bark extract.

[0059] Without the phospholipid coating, polymerization was 9.6 mg / L or 0.48 mg / 50 m Equivalent to L, 10 -4 In one embodiment, OSA progresses rapidly with concentrations above M. , phospholipid coating, 10 -4 Concentrations greater than 0.5 mg / L, e.g. Stabilize solutions of OSA at concentrations above 0.0 mL, especially at concentrations above 0.80 mg / 50 mL. Advantageously, the phospholipid coating may be at least 0.90 mg / 50 mL, e.g. For example, OSA solutions of 0.95 mg / 50 mL or more, especially 1.0 mg / 50 mL or more, can be stably administered. It can be done.

[0060] In one embodiment, the product of the first aspect of the invention (optionally comprising a willow bark extract, and and / or one or more amino acids such as one or more of arginine and glycine) 5% by weight of phospholipids (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, Phosphatidylethanolamine, components of lecithin and one or more of their derivatives, in particular phosphatidylcholine, hydrogenated phosphatidylcholine and one or more of their derivatives) , for example at least 20% by weight based on the total weight of the coated nanoparticles, typically It comprises at least 30% by weight, in particular at least 50% by weight, of phospholipids. The molar ratio of phospholipid to silicon is at least 0.8:1, e.g., at least The molar ratio of phospholipid to silicone is usually at least 1.5:1. A ratio of 2:1 for both has been found to be particularly advantageous.

[0061] In one embodiment, a phospholipid (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, A component of lecithin, phosphatidylethanolamine, and one of their derivatives The above, particularly phosphatidylcholine, hydrogenated phosphatidylcholine and derivatives thereof The phospholipids (one or more) have a number average molecular weight in the range of 500 to 1000. Particularly suitable phospholipids are Particularly suitable phospholipids are those with a polar head group, such as phosphatidylcholine, glycerophospholipids, Binding to a quaternary ammonium moiety such as phosphatidylcholine (PC) or hydrogenated phosphatidylcholine The type of lipid can be selected depending on the properties of the formulation. While lipids are suitable for aprotic formulations, positively charged and small CH 3 The lipid chain is Preferably, the side chain is polyethylene glycol or polypropylene. Aliphatic side chains with 15 or more carbon atoms or 6 or more ether units, such as pyrene glycol chains The repeating ether side chain is

[0062] In one embodiment, a phospholipid stabilizer (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, Phatidylcholine, phosphatidylethanolamine, lecithin components and their derivatives one or more of the above-mentioned substances, in particular phosphatidylcholine, hydrogenated phosphatidylcholine and their derivatives conductor) is electrostatically bonded to the silicon surface by van der Waals forces Preferably, the contact angle of the stabilizing agent is The contact angle of a droplet of the liquid is measured by optical tensiometry, which observes and measures the contact angle of the droplet of the liquid. The contact angle of the ... Preferably, the contact angle is less than 20°, and ideally less than 10°. The smaller the contact angle, the greater the surface and stabilization. The chemical features that result from favorable van der Waals attraction include , hydrogen-saturated molecules such as saturated lipids.

[0063] Phospholipids are amphiphilic in nature, with the "head" being hydrophilic and the "tail" being lipophilic.

[0064] Phospholipids are modified to form a phospholipid bilayer with the head groups facing outward and the lipid tails facing inward. In a preferred embodiment (e.g., the nanoparticles are When coated with one or more of phosphorus, hydrogenated phosphatidylcholine and their derivatives, Such nanoparticles may optionally contain willow bark extract, and / or arginine and glycine. According to the present invention, the nanoparticles can be formed by the above-mentioned method. The phospholipids that coat the surface are formed as a bilayer of phospholipids, e.g., phosphatidylcholine. It exists as a bilayer of phospholipids containing choline or hydrogenated phosphatidylcholine.

[0065] Uses of all aspects of the invention in addition to or as a replacement for phosphatidylcholine Other suitable phospholipids for the preparation of phosphatidylethanolamine and lecithin components include , phosphoinositides (e.g., phosphatidylinositol, phosphatidylinositol phosphate, phosphatidylinositol biphosphate and phosphatidylinositol triphosphate phosphate), ceramide phosphorylcholine, ceramide phosphorylethanolamine and ceramide phosphorylethanolamine. and sphingophospholipids such as mydophospholipids. For example, one of these phospholipids The above is a method for producing a composition comprising the step of: providing a nanoparticle containing willow bark extract and / or one or more of arginine and glycine; The phospholipids used according to the invention may be associated with one or more amino acids. The lipids may of course be used as mixtures of phospholipids. The composition may comprise nanoparticles containing willow bark extract and / or one or more of arginine and glycine. It may be used when associated with one or more amino acids. Phospholipids may also be used as phospholipids, relatively Mixtures with small amounts of non-phospholipid components, such as cholesterol, other lipids or sterols The non-phospholipid components can be used to fine-tune the properties of the phospholipid bilayer. For example, it may be useful to incorporate the phospholipids into the coating. The mixture with small amounts of non-phospholipid components is a nanoparticle of willow bark extract and / or arginine. The phospholipids may be used in combination with one or more amino acids, such as one or more of phenylalanine and glycine. The porous coating is preferably at least 60% phospholipid, e.g. at least 70% or 80% It is preferred that the coating comprises a phospholipid. In certain embodiments, the phospholipid coating comprises For example, the nanoparticles may contain willow bark extract, and / or one or more of arginine and glycine. At least 60%, 70% or 80% of the phosphatidylinositol is The coating comprises at least 80% phosphatidylcholine or hydrogenated phosphatidylcholine. Preferably, the bilayer comprises hydrogenated phosphatidylcholine.

[0066] The nanoparticles of the present invention are prepared by a process that involves the use of fatty acid esters that have been melted and made into a waxy form. A phospholipid coating can be used to produce particles according to the second aspect of the invention. (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidylethanolamine) one or more of the following: amines, components of lecithin and their derivatives, in particular phosphatidylcholine phospholipid coating comprising one or more of hydrogenated phosphatidylcholine and their derivatives. The syrup) is resistant to heating, e.g., 30°C, 35°C, 40°C, 45°C, 50°C, or 55°C. It is preferable to be able to do so.

[0067] The phospholipid coating is a bilayer of phospholipids (e.g., phosphatidylcholine, hydrogenated Phosphatidylcholine, phosphatidylethanolamine, lecithin components and their One or more of the derivatives thereof, in particular phosphatidylcholine, hydrogenated phosphatidylcholine, and derivatives thereof. It is preferred that the bilayer is a phospholipid bilayer containing one or more of the derivatives of phospholipids. The lipid coating was heated at 30°C, 35°C, 40°C, 45°C, 50°C or 55°C for 20 minutes. At least 80% of hydrogenated phosphatidylcholine remains substantially unchanged when heated. The membrane may be a bilayer of phospholipids containing amines.

[0068] Hydrolyzable silicon-containing nanoparticles The product of the present invention comprises silicon nanoparticles, the surface of which is made of phospholipids. Optionally, the silicon nanoparticles are coated with willow and associated with fluorouracil. bark extract, and / or one or more amino acids, such as one or more of arginine and glycine. The nominal diameter of the silicon nanoparticles is 10-400 nm, e.g., 50-350 nm. , for example 80 to 310 nm, for example 100 to 250 nm, for example 120 to 240 nm, e.g. For example, 150 to 220 nm, for example, about 200 nm. Silicon nanoparticles are pure silicon. Silicon nanoparticles are porous and consist of either a hydrolyzable silicon-containing material or a hydrolyzable silicon-containing material. Silicon nanoparticles are preferably prepared by dissolving the particles in a hydrofluoric acid (HF) / ethanol mixture. It can be made porous by standard techniques, such as contacting the mixture with an electric current. By varying the current density and exposure time, the density and size of the pores can be controlled. can be controlled and monitored by scanning electron microscopy and / or nitrogen adsorption / desorption volumetric isotherm measurements. .

[0069] Fluorouracil Fluorouracil can be applied to silicon nanoparticles and / or phospholipid bilayers (e.g., phospholipids). Phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidylethanolamine, One or more of the components of choline and their derivatives, in particular phosphatidylcholine, hydrogenated phosphatidylcholine, Electrostatic interaction with the surface of a bilayer of phospholipids containing acetylcholine and one or more of their derivatives The products of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine) are associated with and optionally a willow bark extract, and and / or silicon nanoparticles associated with one or more amino acids, such as one or more of arginine and glycine. At least 90% of the total fluorouracil in the nanoparticles is comprised of silicon nanoparticles and / or silicon nanoparticles. It is preferred that the fluorophore physically associates with or adsorbs to the surface of the fluorophore lipid bilayer. Less than 10% of the total louracil is free.

[0070] Willow Bark Extract The products of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine and the like) The antibody is coated with one or more of these derivatives, associated with fluorouracil, and optionally with arginine. and one or more amino acids, such as one or more of riboflavin and glycine, The composition may include willow bark extract, which is commercially available from several sources. For example, willow bark extract can be found at 9 Via Petrolo Litta, 20010 Active Co in Bareggio (Milano) Italy Available from Ncepts, Srl. Willow bark extracts typically contain salicin. , the structure of which is shown below.

[0071] [ka]

[0072] Salicin is a β-glucoside and derivative of salicylic acid. Salicin is usually In humans, it is metabolized to salicylic acid. When salicin is metabolized, its acetal ethers are The diol bridge is broken down to produce glucose and salicylic alcohol. It is then produced by oxidation of the alcohol group of salicylic alcohol.

[0073] The willow bark extract is the bark of Willow serrata or White willow, preferably can be extracted from the bark of the willow tree. Willow bark extract is made from crushed willow bark. Alternatively, the powder may be provided in the product of the present invention as a powder, such as powder derived from willow bark. The bark extract may be provided in the product of the invention in a solution, such as an aqueous or ethanolic solution. Liquid willow bark extract is typically colorless to light tan in color.

[0074] Willow bark extract is known to exhibit antioxidant and anti-inflammatory activities. The bark extract can therefore be used as an active ingredient in anti-aging preparations. The extract is usually 8 to 12% by weight of salicin (or more preferably 8 to 12% by weight of salicin). It is often marketed for its analgesic properties because it contains benzodiazepines (benzoyl salts). The commercially available willow bark extracts contain salicin, salicylates or salicylic acid. It is often characterized by the content of % by volume.

[0075] powder According to a second aspect, the present invention provides solid particles of one or more waxy fatty acid esters. The solid particles are then coated with pharma- ceutically compatible nanoparticles according to the first aspect of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine and one or more of their derivatives. and willow bark extract, and / or one or more of arginine and glycine. The powder was a pharma- ceutical compatible powder containing solid particles encapsulated with amine acids (nanoparticles capable of associating with amino acids). More than 65% by weight of the composition of fluorouracil is associated with the coated nanoparticles. The present invention provides a powder in which less than 10% by weight of the composition of fluorouracil is present in the waxy phase of the composition. It is preferred that the fatty acid ester moiety of

[0076] Powders (e.g., powders comprising solid particles of one or more waxy fatty acid esters, The solid particles include phosphatidylcholine, hydrogenated phosphatidylcholine, and derivatives thereof. and encapsulating silicon nanoparticles coated with one or more of the following: The nanoparticles are made of fluorouracil and, optionally, willow bark extract, and / or arginine and The powder (associated with one or more amino acids such as glycine and glycine) has a maximum diameter of 30 to 550 microns. It is preferred that the particles contain approximately spherical particles with a minimum of 90% spherical diameter. The large diameter is 50-500 microns (or 100-500 microns, or 150-400 microns). The solid particles of the powder of the present invention are significantly more porous than the nanoparticles of the present invention. Being large, each particle will typically encapsulate a large number of the nanoparticles of the invention.

[0077] Waxy fatty acid esters (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine) Waxy encapsulating silicon nanoparticles coated with one or more of tetracycline and their derivatives. and the coated nanoparticles are provided with a fatty acid ester of fluorouracil and optionally Optionally, willow bark extract, and / or amino acids such as one or more of arginine and glycine. The melting point of the associated waxy fatty acid ester is 25°C to 45°C, for example 28°C to 42°C. For example, the melting point is preferably 30° C. to 40° C. The melting point is set so that the material melts upon contact with the skin. In certain embodiments (e.g., the waxy fatty acid esters include Phosphatidylcholine, hydrogenated phosphatidylcholine and one or more of their derivatives When the coated silicon nanoparticles are encapsulated, the coated silicon nanoparticles contains fluorouracil and, optionally, willow bark extract, and / or arginine and glycine According to the study, waxy fatty acid esters are associated with one or more amino acids such as stearyl Although they are esters of fatty alcohols, they are also esters of other fatty alcohols, especially alcohols of saturated fatty acids. For example, caprylic acid, decanoic acid, lauric acid, myristic acid, palmitic acid and oleic acid. Esters of acetic acid alcohols may be used. The fatty component of the ester may be heptanoic or caprylic acid. In a preferred embodiment (e.g., a waxy fatty acid ester), , phosphatidylcholine, hydrogenated phosphatidylcholine and derivatives thereof. When the coated silicon nanoparticles are encapsulated, The drug is a combination of fluorouracil and, optionally, willow bark extract, and / or arginine and glycine. According to the study, waxy fatty acid esters are formed by associating with one or more amino acids such as decane, Esters of acids (i.e., cetyl decanoate) and / or or a mixture of stearyl heptanoate and stearyl caprylate. In certain preferred embodiments, the composition further comprises: Contains a mixture of stearyl heptanoate, stearyl caprylate and 1-hexadecanol. Preferably the waxy fatty acid ester has emollient properties.

[0078] Phase transition control agent Example: Limonene and Pluronic® Powders (e.g., powders comprising solid particles of one or more waxy fatty acid esters, The solid particles include phosphatidylcholine, hydrogenated phosphatidylcholine, and derivatives thereof. and encapsulating silicon nanoparticles coated with one or more of the following: The nanoparticles are comprised of fluorouracil and, optionally, willow bark extract, and / or arginine. The powder may optionally be combined with an amino acid such as one or more of limonene, glycine, etc. Terpenes and / or Pluronic® (poly(ethylene glycol)-block -Poly(propylene glycol)-block-poly(ethylene glycol) etc. The surfactant may include

[0079] Limonene serves at least two purposes. First, it is a waxy fatty acid ester. The phase transition temperature of the terbium oxide is adjusted, which is effective in adjusting the final melting point of the solid particles of the powder of the present invention. Limonene acts as a skin penetration enhancer and helps to promote the release of fluorouracil. It can also accelerate the absorption rate of Pluronic (especially Pluronic L-61) etc. The other surfactant is preferably used in addition to limonene rather than as a complete replacement. Limonene, due to its emulsifier properties, also contributes to the effectiveness of the products of the invention. It can also improve the duration and stability. (R)-(+)-Limonene (~90%) is used. It is preferred to use other forms of limonene that are less pure, such as essential citrus oil. can also be used, but in higher concentrations to achieve the same effect.

[0080] Topical creams and gels According to a third aspect, the present invention provides a pharmaceutical composition suitable for topical administration to the skin or other body surfaces. The present invention provides a cream or gel formulation that is compatible with the skin, is a pharma- ceutically compatible powder according to the second aspect of the invention (e.g. one or more waxy fats The solid particles include phosphatidylcholine, phosphatidyl ester, and Encapsulating silicon nanoparticles coated with tidylcholine and one or more of their derivatives The coated silicon nanoparticles are then mixed with fluorouracil and, optionally, willow bark. extracts, and / or powders in association with amino acids such as one or more of arginine and glycine) It comprises a cream base in which the above is suspended.

[0081] FDA and EMA guidelines for maximum levels of fluorouracil in topical formulations The standard specifies a maximum recommended level of 5% by weight total. For example, topical creams or gels may contain up to 5% by weight, up to 6% by weight, up to 4% by weight, up to 3% by weight, %, up to 2%, up to 1% or up to 0.5% by weight of fluorouracil.

[0082] Common doses are 1%, 2% and 5% for the treatment of basal cell carcinoma. The usual dose of is 0.5%. The recommended treatment duration for a 5% dose regimen is 3 to 6 It usually takes about 10 to 12 weeks for the lesions to disappear.

[0083] Pharmaceutically compatible creams contain a cream base. Cream bases are typically oil-in-water The oil phase is a droplet-type or water-in-oil type emulsion. and an emollient, and a majority (e.g., at least 5 0%, 70% or 80%). The above-mentioned terpenes can be found substantially in the aqueous phase. Fluorouracil is present in very small amounts. The amount (e.g., less than 5% or less than 2% by weight of the total fluorouracil) is in a cream or It is present in the aqueous phase of the gel in very small amounts (e.g., less than 5% by weight of the total fluorouracil or 2 It is preferred that less than 1% by weight of the oil phase of the cream is present.

[0084] The pharma- ceutically compatible gel comprises the powder of the second aspect of the invention dispersed in a liquid phase of oil droplets. The gel agent is preferably a crosslinked polymer such as polyethylene oxide or polyacrylamide; Or agarose, methylcellulose, hyaluronic acid, elastin-like polypeptide, carbohydrate Hydrogels (colloidal gels) containing polyacrylic acid, gelatin or collagen (L).

[0085] A hydrophilic matrix (e.g., carbomer gel containing triethanolamine) It may be preferable to use a gel having the following properties, since such a gel, once The waxy fatty acid ester encapsulation is broken and fluorouracil comes into contact with the gel matrix. This can favor a rapid absorption rate of fluorouracil.

[0086] The pharma- ceutically compatible cream or gel according to the third aspect of the present invention contains 0.05 to 4% by weight , 0.05 to 3 wt%, 0.05 to 2 wt%, or 0.05 to 1 wt% fluorouracil etc., may contain 0.05-5% by weight of fluorouracil. Or the gelling agent may contain 1 to 5% by weight, 2 to 5% by weight, 3 to 5% by weight, or 4 to 5% by weight of fluoro Optionally, the pharma- ceutically compatible cream or gel may contain 5 to 15 wt. %, 6-14 wt. %, 7-13 wt. % or 8-12 wt. % salicylate, etc. It further contains 20% by weight of a salicylate.

[0087] Adhesive Patch According to a fourth aspect, the present invention is an adhesive patch comprising a backing layer and an adhesive film. Thus, the adhesive film is coated with a pharma- ceutically compatible powder according to the second aspect of the present invention (e.g., The solid particles include one or more waxy fatty acid esters, the solid particles including phosphatidyl esters. Coated with one or more of choline, hydrogenated phosphatidylcholine and their derivatives The silicon nanoparticles are encapsulated and the coated silicon nanoparticles are treated with fluorouracil. and optionally willow bark extract, and / or one or more of arginine and glycine. a powder in association with amino acids) or a cream or gel according to the third aspect of the invention (the present invention A cream comprising a cream base in which the pharma- ceutically compatible powder according to the second aspect is suspended; or The present invention provides an adhesive patch comprising a gel.

[0088] The patch according to the invention is typically a transdermal patch and may be textile, polymeric or paper. a backing layer that provides support and protects the patch from the external environment, and optionally a membrane, e.g. It consists of a polymer membrane that prevents uracil from passing through the backing layer, and an adhesive. Rasil may be a powder according to the second aspect of the invention or a cream according to the third aspect of the invention. The fluorouracil-containing product is preferably present in the form of an adhesive or gel. or, if fluorouracil is contained in a gel, the gel can act as a reservoir in a patch product (a so-called "monolithic" device). It is preferred that the fluorouracil-containing product is present in the adhesive layer.

[0089] Patches reduce the likelihood of careless or improper use by the end user. In addition, patches can be useful in ensuring correct dosing of the treatment area. is limited to avoid unintended spread to other areas.

[0090] treatment The products of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine and the like) Nanoparticles coated with one or more of these derivatives, the nanoparticles being fluoro In association with lauracil and further comprising willow bark extract, and / or one of arginine and glycine The nanoparticles, which can be combined with one or more amino acids, are effective in treating superficial basal cell carcinoma, actinic keratosis, and sunburn. It is suitable for use in the treatment of conditions including keratosis and scarring. These include ointment scars, hypertrophic scars and post-surgical scars. The products of the present invention may also be used to treat acne. , and may also be used to treat severe acne.

[0091] Suitable dosages for basal cell carcinoma are 1%, 2% and 5% (by weight of product). Even smaller doses, such as 0.25% to 1% or 0.1% to 0.5%, may be used in other conditions. For example, this may be appropriate for scars.

[0092] Combination treatment In addition to the fluorouracil product, the present invention includes one or more additional active ingredients. Alternatively, the methods of the invention may include the use of another active ingredient (API). Another API can be conveniently formulated at the same time as fluorouracil (e.g., another API I is one or more of phosphatidylcholine, hydrogenated phosphatidylcholine and their derivatives. The nanoparticles coated as above, in such embodiments, also comprise Nagi bark extract and / or can be combined with amino acids such as one or more of arginine and glycine (It can be co-formulated with fluorouracil for delivery via nanoparticles that can be used to treat basal cell Other APIs suitable for the treatment of follicular carcinoma include imiquimod, vismodegib and curcumin. Other APIs that are particularly suitable for treating keratosis include imiquimod, ingenol mebutate, , diclofenac, retinoids (e.g., adapalene, tazarotene, retinol, isotonic acid, Retinoin, acitretin and tretinoin) are especially useful in the treatment of keloid scars. Other suitable APIs include salicylates, corticosteroids, and interferons. Other APIs that are particularly well suited for treating acne include azelaic acid, benzoyl peroxide, and salicylic acid. Antibiotics, retinoids, nicotinamides and antihistamines or alternatives Natural extracts of each of the sources, namely willow bark extract, are included.

[0093] Treatment planning The products of the present invention (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine and the like) The nanoparticles include nanoparticles coated with one or more of these derivatives, the nanoparticles being fluoro. In association with uracil and willow bark extract, and / or one of arginine and glycine The above-mentioned amino acid-associated products and methods may be used in any administration deemed appropriate. For example, treatment may be continued until the disease is cured or for a period of time beyond that. The usual course of treatment for keratosis can be continued until no further improvement is observed. The plan lasts for 3 to 20 weeks, for example, 3 to 12, 5 to 15, or 5 to 12 weeks. It may be used under the following conditions.

[0094] Silicon-containing materials As used herein, the term "hydrolyzable silicon-containing material" means Any silicon-containing material that can be hydrolyzed to OSA upon administration to a human or animal subject. Typically, 1 mg of nanoparticles of hydrolyzable silicon-containing material is dissolved in a physiological buffer, e.g. For example, the silicon-containing polymer of the present invention is hydrolyzed in 100 mL of PBS at 37° C. for 1 hour. The material contains at least 50% silicon by weight. For example, the silicon-containing material of the present invention is The silicon-containing material is substantially pure silicon. For example, at least 90% by weight of silicon, preferably at least 95% by weight of silicon. The hydrolyzable silicon may be a material containing at least 99% by weight of silicon. Silicon-containing materials are typically semiconductor materials such as amorphous silicon. The silicon in the powder is usually of high purity, e.g., at least 99.99% by weight silicon. The substantially pure silicon material may contain other elements, for example as semiconductor dopants, and optionally It may contain trace amounts of boron, arsenic, phosphorus and / or gallium. Substantially pure silicon The material may be, for example, P-type doped silicon containing trace amounts of boron or another group III element. Wafers, or N-type silicon wafers containing trace amounts of, for example, phosphorus or another Group VI element. The surface of a silicon material typically contains silanol (Si-OH) groups. Hydrolyzable silicon-containing materials suitable for use in accordance with the present invention include, but are not limited to, semiconductor grade silicon-containing materials. nanosilicon (monocrystalline or polycrystalline) and nanosilicon.

[0095] Suitably, the product of the invention (e.g. phosphatidylcholine, hydrogenated phosphatidylcholine) is The nanoparticles are coated with one or more of phosphorus and its derivatives, , in association with fluorouracil, and further containing willow bark extract, and / or arginine and glycol The silicon content of the product (which can associate with one or more amino acids such as sucrose) is 0.01 to 5 0% by weight, preferably 0.01 to 10% by weight, and more preferably 0.1 to 1 0% by weight, and most preferably in the range of 0.1 to 5% by weight. The silicon content of the composition is 1 to 30% by weight, for example 2 to 30% by weight, based on the total weight of the composition. 20% by weight, preferably in the range of 3 to 15% by weight.

[0096] Nanoparticles For the purposes of the present invention, the term "nanoparticle" refers to particles that are typically in the nanometer range. have at least one size within the range of 300 nm or less, i.e., 300 nm or less, and behave identically to nanoparticles and characteristics for use in accordance with the present invention. Nanoparticles of phosphatidylcholine, hydrogenated phosphatidylcholine and their Nanoparticles coated with one or more of the derivatives of fluorouracil, and / or one or more of arginine and glycine. The nanoparticles (which can also be associated with one or more amino acids) usually have an average particle size of less than 300 nm, preferably In one embodiment, the average diameter of the nanoparticles is less than 200 nm, and in particular less than 100 nm. The average particle size is 10 to 100 nm, preferably 20 to 80 nm, and particularly preferably 10 to 50 nm. In this embodiment, the average particle size of the nanoparticles is 50 to 200 nm, 60 to 250 nm, or In a preferred embodiment (e.g., silicon nanoparticles are The coated surface is coated with one or more of phosphatidylcholine, hydrogenated phosphatidylcholine and their derivatives. Upon contact, these nanoparticles are combined with fluorouracil, optionally with willow bark extract, and and / or one or more amino acids, such as one or more of arginine and glycine The average particle size of the nanoparticles is 30 to 100 nm. It is understood that the particles are not necessarily spherical in size. Particle size is conveniently expressed as: This can be measured using conventional techniques, such as microscopic techniques, for example scanning electron microscopy.

[0097] In some embodiments, silicon particles (e.g., Phosphatidylcholine, hydrogenated phosphatidylcholine and one or more of their derivatives Silicon particles coated with fluorouracil, , willow bark extract, and / or one or more amines such as one or more of arginine and glycine. The average particle size of the silicon particles (which can also be associated with carboxylic acid) is less than 1000 μm, for example, 1 to 10 The thickness can be 00 μm, 100 to 1000 μm, or 500 to 1000 μm. The average particle size of the nanoparticles is less than 500 μm, for example, 1 to 500 μm or 100 to 500 μm. The average particle size of the silicon particles can be less than 50 μm, for example, 1 to 50 μm. Or, the average particle size of the silicon particles may be less than 10 μm, e.g., 25 to 50 μm. For example, it can be 1 to 10 μm or 5 to 10 μm.

[0098] In some embodiments (e.g., silicon nanoparticles are combined with phosphatidylcholine, hydrogen peroxide, When coated with one or more of the phosphate phosphatidylcholines and their derivatives, these The nanoparticles are associated with fluorouracil and, optionally, willow bark extract, and / or alginate. and one or more amino acids, such as one or more of riboflavin and glycine, Nanoparticles are spherical or substantially spherical in shape. The shape can be determined by conventional optical or electron microscopy techniques. It is advantageous to be able to evaluate the

[0099] Preparation of silicon-containing nanoparticles The silicon-containing nanoparticles in relation to the present invention can be advantageously prepared by conventional techniques in the art. The granules can be prepared, for example, by milling or other known techniques for reducing particle size. The silicon-containing nanoparticles may be sodium silicate particles, colloidal silica or silicon wafers. The macro- or micro-scale particles are produced by ball milling, planetary ball milling, and press milling. The resulting material is then crushed by plasma or laser ablation or other crushing mechanisms. The collected particles are air classified to recover the nanoparticles. Laser ablation can also be used.

[0100] Porous nanoparticles can be prepared by techniques conventional in the art, including the methods described herein. It can be prepared as follows.

[0101] Addition of phospholipids Stabilizing phospholipids (e.g., phosphatidylcholine, hydrogenated phosphatidylcholine, Phosphatidylethanolamine, components of lecithin and one or more of their derivatives, in particular , phosphatidylcholine, hydrogenated phosphatidylcholine and one or more of their derivatives) Prior to the addition of the porous nanoparticles, they are "activated" to improve the adhesion of the phospholipids. Activation can be carried out by any suitable means. For example, The particles are dissolved in a volatile solvent (e.g., ethanol, methanol, acetone, or Instead, the porous nanoparticles can be washed with volatile solvents that are miscible with water. Wash with a solvent (e.g., an alcohol such as ethanol), then wash in water, and freeze-dry. The drying step is carried out to dryness.

[0102] Phospholipids can then be added to the activated nanoparticles. The nanoparticles are dissolved in a volatile solvent such as alcohols such as methanol and ethanol. After mixing, the solvent is evaporated while the particles are stirred (e.g., using a rotary evaporation system). It is preferable that the above-mentioned step be carried out by

[0103] Powder preparation The powder is made of nanoparticles coated with phospholipids (e.g., phosphatidylcholine, hydrogen peroxide). Phosphatidylcholine, phosphatidylethanolamine, lecithin and their components The nanoparticles are coated with one or more of the derivatives of fatty acid esters, which are melted and turned into wax. ster or mixtures thereof (preferably at 30°C, 35°C, 37°C, 40°C, 45°C, 50°C or below 55°C) and mix. The waxy fatty acid ester is The mixture is then coagulated by any suitable means, such as coagulating and grinding or emulsifying and coagulating. The addition of terpenes such as limonene can aid in emulsification.

[0104] Terpenes can also promote a phase transition state throughout the formulation. Some lipids that may constitute the fatty acid esters or mixtures thereof may be administered to the skin. The use of terpenes is not toxic to the skin. When administered, these particles melt due to body heat or the friction caused by rubbing the powder on the skin. This is advantageous for

[0105] Preparation of creams and gels Creams and gels are simply powders dispersed (i.e., mixed) in a cream or gel base. For example, the powder can be mixed with a pharmaceutical cream base. For gels, the powder can be placed in powder form in the gel matrix and stirred. It can be stirred and then the gel hydrated or stirred into a pre-hydrated gel.

[0106] Preparation of patches The patch can be formulated by any suitable method, for example, by preparing a mucoadhesive aqueous gel. A patch containing the powder of the present invention can be prepared by dispersing the powder therein. The gel may be optionally formed by gently evaporating water to form a film having the required adhesive properties. It can be dried by evaporating. EXAMPLES

[0107] The present invention can be further illustrated by the following non-limiting examples.

[0108] material Distilled water, cetyl decanoate, limonene, sodium bicarbonate Lithium, 5-fluorouracil (5FU), 1-hexadecanol, activated silico Silicon nanoparticles (SiNP, 100 nm), hydrogenated phosphatidylcholine (PHOSPHOL IPON® 90 G, yellowish waxy material - hydrogen only soluble in EtOH Phosphatidylcholine), distilled water, ethanol.

[0109] Preparation of silicon Single-sided polished P-type or N-type silicon wafers are purchased from Si-Mat, Germany. All cleaning and etching reagents are of clean room grade. Resistivity is 0.005. Vcm -1 A P++ type Si(100) wafer of 200 nm was used as the substrate. Silicon layers were deposited by low pressure chemical vapor deposition. Standard photolithography was used. The porous nanoparticles were patterned using an EVG620 contact aligner. The particles were incubated for 8 h in a mixture of hydrofluoric acid (HF) and ethanol (3:7 v / v). 0mA cm -2 A high porosity layer was formed by applying a current density of 1000 s for 25 s. , 320 mA in a mixture of 49% HF:ethanol at a ratio of 2:5 (v / v) cm -2 Smaller holes were formed by applying a current density of 1000 s for 6 s. 49%) and ethanol mixture (3:7 v / v), at 80 mA cm -2 Current density In a particular case, the pores were formed by applying a 25 s high temperature. In a mixture with ethanol (1:1 v / v), 6 mA cm -2 The current density is 1.7 The nitride layer was removed by HF and then isopropanol was added. The particles were released by sonication in alcohol for 1 minute. The shape was roughly semicircular. The pore size is determined by the nitrogen absorption and desorption. The volume of the etched sample can be measured by isothermal analysis. After etching, the sample is immersed in pure ethanol. and dried under a stream of high purity dry nitrogen before use.

[0110] Etched silicon wafers, P+ or N-, are crushed in a ball mill and / or crusher and pulverized. The powder was crushed using a crusher. The fine powder was measured using a Retsch brand 38 μm sieve scale. The particles were sieved using a shaker AS200. The selected sizes (20-100μ) were The uniformity in particle size (μm) is achieved by the size of the sieve openings. Measured using a Chrome device and a Malvern Instruments PCS. The samples were stored in sealed containers until further use.

[0111] Nanosilicon powder was also obtained from Sigma and HefeI Kaier, China. The grain size was measured by PCS and recorded before filling and etching (size range: 20–100). Silicon wafers were milled using a ball mill or crushed with a grinder and The powder was crushed using a crusher. The fine powder was measured using a Retsch brand 38um sieve. The nanoparticles were sieved using a sieve and shaker AS200 to obtain uniform nanoparticles of the desired size. It was recovered.

[0112] Activation of silicon nanoparticles 250 mL of ethanol and 500 mg of porous silicon nanoparticles with a particle size of 30 to 100 nm The mixture was mixed and stirred for 30 minutes. The solution was then centrifuged at 3000 rpm for 30 minutes. The supernatant was discarded and the nanoparticles were washed with 5 mL of distilled water and transferred to a round-bottom flask. The contents of the LASCO were frozen (-25°C for 2 hours). The frozen nanoparticles were lyophilized overnight. The resulting dry powder was freeze-dried using a freeze-drying machine. He is a child.

[0113] Instead, 250 mL of methanol and 50 mL of porous silicon nanoparticles with a particle size of 30 nm were used. The mixture was mixed with 100g of ... The organic solvent residue was then completely evaporated (24 hours at room temperature). Once obtained, this layer was crushed and ground to obtain a powder. The resulting dry powder was functionalized silicon nanoparticles.

[0114] Stabilization of hydrogenated phosphatidylcholine by bilayer membranes. 150 mg of hydrogenated phosphatidylcholine was dissolved in 30 ml of ethanol. The samples were dried (at least 5 min) by connecting to a rotary evaporator at 45°C.

[0115] Liposome rehydration and fluorouracil loading 15 mg of the stabilized nanoparticles were transferred to a beaker and 300 mg of fluorouracil was added. 20 mL of distilled water was added to the mixture and the contents of the beaker were sonicated for 5 min. The mixture was homogenized at 30°C for 1 min and then vortexed.

[0116] Drying of fluorouracil-loaded and stabilized particles The solution obtained by the above method was cooled in a refrigerator (at least 2 hours at 4°C) and then frozen. (-20°C for at least 4 hours). The frozen solution was lyophilized overnight to obtain a powder, which was then These stabilized particles were then directly dispersed in a suitable gel. or optionally further coated to alter the release kinetics of the API. Optionally, the particles can be further associated with a willow bark extract (as used in the present invention). The particles are further associated with willow bark extract (see protocol below).

[0117] Production of powders containing fluorouracil nanoparticles Add 1.00 g of 1-hexadecanol and 0.7 g of cetyl decanoate to a 250 mL tall flask. The fluorouracil-loaded particles (i.e., prepared as described above) were transferred to a beaker. powder was added to a beaker. In a separate beaker, 120 mL of distilled water was boiled and Then, 1.0 g of sodium bicarbonate was added together with 2 mL of a phase transition inhibitor. The beaker containing cetyl decanoate and 5FU in xadecanol was poured into a container with a handle, and the contents were then poured into a container with a handle. The Polymix rotary mixer was placed in a cooling enclosure around the The mixture was prepared with ice cubes and acetone. The oily liquid mixture was transferred to a beaker. The mixture was placed in a Polymix mixer at 930 rpm. The solution of the agonist was added to the oily liquid. After 30 seconds, the mixer speed was set to 830 rpm and the mixture was stirred for 1 The mixture was cooled externally for 5 minutes. The resulting powder was filtered out of the solution. It took about 5 to 6 days for the material to dry.

[0118] Patch manufacturing - Disperse 1.0 g of hypromellose powder in 40 mL of pre-warmed distilled water and place in a beaker. was placed in an incubator (T=40° C., magnetic stirring rpm=7) for 3 hours. - When the resulting suspension is opalescent, stop the magnetic stirring and remove the flask from the incubator. Remove the container and allow the samples to cool at room temperature before transferring them to a refrigerator and leaving them overnight. - Once the temperature reaches 4°C, add 0.25g of Pluronic. - The resulting mixture is gently mixed and purified water is added up to 50 mL. - Store the sample in the refrigerator until use. This gel is a synthetic preparation containing an appropriate amount of 5FU. Please note that it is necessary to dilute the powder with 50 ml of water separately from the powder. Weigh out the required amount and gently disperse it in 15 mL of gel. Homogenize to ensure that the amine is evenly distributed throughout the gel. The final concentration of the gel was [hypromellose 1.0% and Pluronic L-61 0.25% ].

[0119] method -Weigh out 0.05g of EDTA and add it to a suitable beaker with 20ml of water (preheated to 60°C). Disperse in L. Stir until complete solubilization. -Weigh out 0.05g of PVP (polyvinylpyrrolidone) K90 and disperse it in the above solution. Stir until completely dissolved. - Weigh out 0.80 g of Natrosol® (hydroxyethyl cellulose); Disperse in the above solution and gently stir. -Weigh out 0.15g of trehalose and disperse it in the above solution. Gently disperse until homogenous. Stir. -When the product has reached room temperature, add 15 mL of distilled water and 0.5 mL of limonene and gently Stir. - Sonicate the above solution for 2 hours. -Weigh 5.0 g of the above viscous solution into a beaker. - 0.4 g of the powder according to the invention prepared as described above was obtained by filling with fluorouracil. Add to the viscous gel and gently stir. -The viscous solution obtained by mixing with the powder was poured into a silicone slot mold (4.5cm x 4.5cm Then, transfer it to a thermostatic bath (30°C, 15-35% RE) and leave it for 20 hours. The resulting film is loaded with the powder of the present invention and is ready for administration to the skin, and can be attached to a suitable backing. A further layer may be provided: a mucoadhesive membrane.

[0120] Preparation of silicon nanoparticles associated with willow bark extract. 0.5 wt% fluorouracil and 10 wt% willow bark extract loaded with nanoparticles An exemplary protocol for preparing nanoparticles comprising:

[0121] [Table 1]

[0122] Preparation of hydrogenated phosphatidylcholine (PC) stock solution (solution A) Dissolve 24 mg of -PC6 in 250 mL of ethanol and sonicate. The final concentration is 2.5 mg / mL.

[0123] Preparation of solution for rehydration of PC-willow bark dry foam (solution B) -Add 16 mg of activated silicon nanoparticles (SiNPs) (30 nm) to the beaker. -Add 4 mg of arginine to the beaker. Then add 2 mg of glycine to the beaker. . -Fluorouracil 1500mg was added to the same solution containing SiNPs, arginine and glycine. Add to the beaker. - Disperse this mixture in 200 mL of distilled water by stirring for 15 minutes.

[0124] Lipid-based thin-film PC-willow bark using phosphatidylcholine and willow bark extract Formation of leather dry foam - Dissolve 624 mg of hydrogenated phosphatidylcholine in 250 mL of ethanol and then heat in a water bath. The mixture is then sonicated in a 350 rpm flask at 45°C for at least 10 minutes. Move it to ko. -Add 30 mL of willow bark extract to a round bottom flask. -Connect the round bottom flask to a rotary evaporation system. - Maintain rotary evaporation at maximum speed for 45 minutes (at room temperature). - Reduce the temperature to -45° C. Allow the samples to dry for at least 15 minutes. -The product appears as a thick white foam.

[0125] Rehydration of lipid-based dry foam of PC-willow bark -Add 16 mg of activated silicon nanoparticles (SiNPs, size 30 nm) to the beaker . -Add 4 mg of arginine to a beaker. Then add 2 mg of glycine to the same beaker. Add. -Fluorouracil 1500mg was added to the same solution containing SiNPs, arginine and glycine. Add to the beaker. - Disperse this mixture in 120 mL of distilled water by ultrasonic treatment for 5 minutes at 30°C. To make. -Vortex the solution to homogenize the ingredients. - Add the solution to the round bottom flask containing the formulation of dry foam (PC and willow bark extract) Add. Vortex until foam is fully dissolved. - Rinse the round bottom flask with 10 ml of distilled water. - The resulting dissolved foam (total volume 130 ml) is sonicated for 30 minutes at 30°C. -Place in the fridge for 1 hour, then transfer to the freezer (at -25°C) for approximately 3 hours. -Dry powder by connecting the tube to a freeze-drying apparatus for at least 3 days to evaporate the solvent get. The resulting powder can be stored for reconstitution with purified water or mixed with a suitable solvent. Optionally, the freeze-drying step can be omitted and the sonicated dissolved foam can be directly It can be mixed with the desired solvent.

[0126] Preparation of gel for dispersion of final product [Table 2] - Disperse 1.0 g of hypromellose powder in a beaker containing 40 mL of distilled water. The car is placed in an incubator (40° C., magnetic stirring at 7 rpm) for 3 hours. - When the resulting suspension is opalescent, remove the gel from the incubator and stop stirring. Stop and allow the samples to cool to room temperature. Transfer to a refrigerator (4°C) and store overnight. - Once the gel has cooled to 4°C, add 0.25 g of Pluronic L-61. L-61 is a masking agent that utilizes a cloud point in the range of 20 to 24°C. - The resulting mixture is mixed gently and up to 50 mL of distilled water is added. - Store the samples in the refrigerator until use. This gel is a pure solution of silicon nanoparticle suspension. 50 ml of medium, equivalent to 1.0% hypromellose and 0.25% Pluronic L-61 It must be diluted to a concentration.

[0127] Preparation of the final product - Disperse the powder in 150 mL of distilled water. The powder is 3 g of salicylic acid in 150 mL of distilled water. 16 mg of silicon nanoparticles, 624 mg of PC, and 1500 mg of 5-fluorouracil. g, 4 mg arginine, and 2 mg glycine in equivalent amounts to willow bark extract. . - 150 g of gel are added to this dispersion. -The mixture is homogenized by vortexing for 20 minutes. -Store the final product at 4°C.

[0128] Another embodiment For the following examples, silicon nanoparticles were mixed with lipids as shown in the protocol above. (PC), willow bark extract, arginine, glycine, fluorouracil, and hyaluronan. The formulation was prepared by associating promellose with a gel containing Pluronic L-61. Dispersed in distilled water with EDTA.

[0129] Cytotoxicity assay of silicon nanoparticles associated with fluorouracil and willow bark extract Assays were set up to test the cytotoxicity of the formulations. The results are presented below and are summarized in Table 1. This shows that the cells were 100% lysed. It has been determined that the biological activity is retained when associated with the nanoparticles of the present invention.

[0130] [Table 3]

[0131] Preservative effectiveness test (PET) The formulation is based on the current United States Pharmacopoeia (USP) <51> Category II Preservative Efficacy Test (ant imicrobial preservatives effectiveness est) and USP <61> The test was conducted using a preservative effectiveness test that conforms to the compatibility test. Pathogen growth tests for the following bacteria, yeasts and molds are included: Group 1 S. aubergine reus ATCC 6583, Group II P. aeruginosa ATCC 9027, group III A. brasiliensis ATCC 16404 , group IV C. albicans ATCC 10231, group V E. coli ATCC 8739. Results are PET pass for bacteria and yeast / mold counts. The results are shown.

[0132] [Table 4]

[0133] Skin sensitization test in guinea pigs (GLP test) The Magnusson-Kligman sensitization test was carried out on guinea pigs to confirm the efficacy of the present invention. It was determined whether fluorouracil-associated nanoparticles induce skin sensitization reactions. The study included intradermal and topical induction and induction phases. The study met the following criteria: American National Standards Institute / Association for Medical Instrumentation / International Organization for Standardization (ANSI / AAMI / ISO) 10 993-1-Biological Evaluation of Medical Devices-Part 2: Animal Welfare Requirements and ANSI / AAMI / ISO 10993-10-Biological evaluation of medical devices-Part 10: Irritation and skin sensitization Sexuality test.

[0134] Results were obtained at any test site at 24 or 48 hours after removal of the challenge patch. Based on these results and the evaluation system, The nanoparticles of the present invention formulated with fluorouracil are not considered to be contact sensitizers. do not have.

[0135] [Table 5]

[0136] [Table 6]

[0137] Clinical Safety Test for Evaluation of Skin Irritation / Sensitization in Humans (Cumulative Irritation and Sensitization Test - RIPT) ) All human skin clinical trials were double-blind studies conducted in human patients (n=52). Test safety for skin irritation / sensitization evaluation (Cumulative Irritation and Sensitization Test - RIPT) ) In human subjects, 0.2 ml of the test substance was directly applied to the designated area of ​​the subject's skin and then blown over. This was continued for 3 days per week until a series of 9 consecutive patch areas were applied. This was repeated for three weeks. Then, subjects were given the substance when there were 10 to 14 days left in the period. Further doses were administered and further evaluations were conducted at 24 and 48 hours.

[0138] The evaluation system is as follows: 0 - Not valid 0.5 - (barely perceptible) Minimal (light pink) uniform or patchy erythema 1 - (Mild) Pink, uniform erythema covering most of the contact area 2 - (Moderate) Pink / red erythema uniformly seen over the entire contact area 3 - (marked) Bright red erythema with edematous petechiae or papules 4 - (Severe) Dark red erythema with vesiculation or blisters with or without eczema

[0139] In the skin irritation evaluation by 24-hour patch test using occlusive patches, all 52 subjects showed no signs of irritation. The score was 0 (zero), which means there were no adverse reactions of any kind during the course of the study, and no cases of erythema. Test substances formulated according to the present invention are therefore not considered to be "non-primary irritants" when administered to the skin. is considered "quality."

[0140] Cumulative Irritation and Sensitization Test (RIPT) Skin Irritation / Sensitization Evaluation All 52 subjects were The scores at the 0, 24, and 48 hour evaluations were zero (0). There were no adverse reactions of any kind during the study. Therefore, it is considered a "non-primary irritant" and a "non-primary sensitizer" to human skin.

[0141] In vivo activity of silicon nanoparticles associated with fluorouracil and willow bark extract. Tro permeation test The nanoparticles according to the invention were treated with varying amounts of fluorouracil and / or willow bark extract. Three such formulations were prepared (see Table 1). Fluorouracil 5% by weight, stearyl alcohol, white petrolatum, and polysol. Bate 60, propylene glycol, methyl paraoxybenzoate, and paraoxybenzoate Efudex cream containing propyl acetate and purified water was used.

[0142] [Table 7]

[0143] The permeability of each sample through human skin was evaluated using an in vitro permeation test (IVPT). The perfusion profile was examined over a 24 hour period. Table 2 below shows the receptor activity over time. The amount of fluorouracil detected in the donor chamber and the receiver during IVPT The amount of fluorouracil that passed through the skin membrane between the Scepter chamber and the septa is shown in Table 2. and blq stands for lower limit of quantification.

[0144] [Table 8]

[0145] As shown in Table 2, fluorouracil suspended in conventional Efudex cream: However, the fluorouracil associated with the nanoparticles of the present invention can easily pass through the skin membrane. The drug does not cross the skin in this manner because it is delivered to the skin in a more tightly controlled manner. When willow bark is used in association with the nanoparticles of the present invention, delivery to the skin is Although still controlled (compared to ex), the permeation rate into each of the layers of the skin is This is slightly faster than the nanoparticles of the present invention without Nagi bark.

[0146] The permeation profile of each sample was analyzed in each layer of the skin after 24 hours. The results are shown in Table 3.

[0147] [Table 9]

[0148] As shown in Table 3, fluorouracil (5 % fluorouracil (by weight) easily passes through the skin membrane without being trapped in any skin layer. When fluorouracil is associated with the nanoparticles of the invention (S1, 5% by weight of fluorouracil), Uracil) and fluorouracil are more controlled and released in smaller amounts into the epidermis. The concentration of fluorouracil is reduced, and fluorouracil does not reach the receptor fluid. (S3, 0.5 wt.% fluorouracil), no release of fluorouracil was observed. However, when the willow bark extract was associated with the nanoparticles of the present invention (S2, 0 0.5% by weight of fluorouracil), the controlled release of fluorouracil is and fluorouracil enters the receptor fluid in small amounts.

[0149] In vitro Franz cell permeation assay Conventional Efudex cream (5% by weight fluorouracil) has also been shown to be effective in preventing inflammatory bowel disease in vitro. In the Franz cell permeation test, S2 (10% by weight of willow bark extract, 0.5% by weight of After 24 hours, tissue samples were collected and the layers of skin tissue were separated. The results showed that fluorouracil was extracted and biochemically quantified in the layers of skin tissue. The degree of localization of fluorouracil and the degree of penetration of the drug into skin tissue samples were determined. The tissue samples included samples collected from the stratum corneum, epidermis and dermis.

[0150] In the case of Efudex, fluorouracil may not be present in the stratum corneum, epidermis, or dermis. Fluorouracil 3.55% applied in Efudex cream penetrates the skin layers. This means that the conventional Efudex cream penetrated the stratum corneum. Fluorouracil that penetrates the 100% dermal layer rapidly penetrates the remaining layers of the skin in an uncontrolled manner. This suggests that:

[0151] In the case of S2, fluorouracil was not found to be present in the stratum corneum or epidermis. However, 10.13% of the applied fluorouracil in S2 was present in the dermis. However, only 0.73% of the drug penetrated the entire skin. When fluorouracil associated with the nanoparticles of the present invention was applied, it was dispersed in a cream base. Conventional creams (such as Efudex) that simply contain suspended molecules of fluorouracil These results suggest that the drug penetrates the skin in a more controlled manner compared to the conventional methods.

Claims

1. 1. A pharmaceutical composition for use in the treatment of superficial basal cell carcinoma, actinic keratosis, solar keratosis, acne or scarring, comprising: The pharmaceutical composition comprises pharma- ceutical compatible nanoparticles and at least 0.5% by weight of fluorouracil; said nanoparticles comprising at least 50% by weight of hydrolyzable silicon; the nanoparticles are surface-coated with a phospholipid, the coated nanoparticles are associated with fluorouracil; the fluorouracil is electrostatically associated with the surface of the nanoparticle and / or phospholipid bilayer; The pharmaceutical composition, wherein the nanoparticles are associated with a willow bark extract.

2. 2. The pharmaceutical composition of claim 1, wherein the phospholipid comprises one or more of phosphatidylcholine, hydrogenated phosphatidylcholine, phosphatidylethanolamine, lecithin moieties, phosphoinositides, sphingophospholipids and derivatives thereof.

3. The pharmaceutical composition of claim 1 or 2, wherein the pharma- ceutically compatible nanoparticles are porous.

4. The pharmaceutical composition of any one of claims 1 to 3, wherein the phospholipid coating comprises a bilayer of phosphatidylcholine.

5. The pharmaceutical composition of any one of claims 1 to 4, wherein the nanoparticles are associated with one or more amino acids.

6. The pharmaceutical composition of claim 5, wherein the one or more amino acids are selected from arginine and glycine.

7. The pharmaceutical composition according to any one of claims 1 to 6, wherein the scar is selected from one or more of keloid scars, hypertrophic scars and post-surgical scars.

8. The pharmaceutical composition according to claim 7, wherein the scar is a hypertrophic scar.

Citation Information

Patent Citations

  • cosmetic composition

    JP1999513036A

  • Delivery system containing silicon

    JP2013500323A

  • Fluorouracil-containing formulation

    US6670335B2

  • A delivery system comprising a silicon-containing material

    WO2011012867A1